ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA SMP KELAS UNGGULAN DAN KELAS REGULER - Evi Sri Rizky; Lailatul Fajriyah; Reka Nurhasanah; Sarah Isnaeni; Delifya Bunga; Wahyu Hidayat (Journal on Education, 2019)
This study aims to analyze the comparison of mathematical reasoning ability between superior grade students and ordinary class students by doing problem test on the material of Two Variable Linear Equation System (SPLDV). This research was conducted in SMP Negeri 5 Cimahi by using quantitative descriptive method. The population in this research is the students of class VIII who have studied the material of Two Variable Linear Equation System (SPLDV). The sample of this research is class VIII-J as superior class and class VIII-K as regular class. To obtain the results of this study using the instrument of test students' mathematical reasoning abilities of 5 items, where each problem has a different level of difficulty